Equine Anti-Thymocyte Globulin (ATGAM) administration in patient with previous rabbit Anti-Thymocyte Globulin (Thymoglobulin) induced serum sickness: A case report - Pryor, Joseph B; Olyaei, Ali J; Lockridge, Joseph B; Norman, Douglas J (Journal of Clinical Nephrology, 2018)
Thymoglobulin is a rabbit-derived anti-thymocyte antibody directed at T-cells and commonly used for induction immunosuppression therapy in solid organ transplantation, especially in immunologically high risk kidney transplant recipients. Despite its frequent use and efficacy, the heterologous makeup of thymoglobulin can induce the immune system resulting in serum sickness which typically presents with rash, fever, fatigue, and poly-arthralgia in the weeks following drug exposure. ATGAM is another anti-thymocyte antibody, targeting the same epitopes, but differs from thymoglobulin by the animal in which the preparations are generated (equine vs. rabbit). Herein, we present a case of a patient with a known history of thymoglobulin-induced serum sickness, who presented with evidence of acute cellular and vascular rejection at their 12-month post-operative visit. Given their immunologically high risk status, they were successfully treated with ATGAM with improvement in their rejection and kidney function. To the author’s knowledge, this is the first case report of successful administration of ATGAM in a patient with a documented history of thymoglobulin induced serum sickness, demonstrating a possible treatment option for acute rejection in patients with reactions to thymoglobulin.